PENGEMBANGAN KOMPETENSI GURU PENDIDIKAN AGAMA ISLAM MELALUI MUSYAWARAH GURU MATA PELAJARAN (MGMP) GURU BERKARAKTER DI KOTA BANDUNG - humaedi ediansyah (Pergunu Jawa Barat, 2021)
ABSTRACT The purpose of this research is to find out is the development of Islamic religious education teacher competence through the subject teachers' consultation (MGMP) for teachers with character in SMA Al-Islam and SMA Kifayatul Achyar in Bandung. The background of this research is that based on preliminary research on several high schools in the city of Bandung, it shows that the development of Islamic religious education teacher competence through (MGMP) which is characterized by this is because it has not been optimal in planning, implementation and evaluation so that it has a negative impact on the development of Islamic religious education teacher competencies. The purpose of this study was to obtain an overview of the planning, implementation, evaluation, problems and solutions of Islamic teligious education teacher competency development through the Subject teacher Consultation (MGMP) of teachers with character in SMA Al-Islam and SMA Kifayatul Achyar Bandung city. Theological basis, Jean Piaget is a cognitive psychology figure who had a great influence on the development of thinking of other cognitive experts. According to Piaget, cognitive development is a genetic proces, which is a process based on the biological mechanism of the development of the nervous system. The philosophical foundation uses the philosophy of constructivism, the theoretical basis uses the theory of teacher values ??with character. This study used a qualitative approach and data collection techniques were carried out through triangulation of observations, interviews and documentation studies, while the source of data was through triangulation of principals, teachers and students. The results of the study show: First, in the planning aspect of Islamic Religious Education Teacher Competency Development Through Subject Teacher Consultations (MGMP) teachers with character in SMA Al-Islam and SMA Kifayatul Achyar, Bandung City. Theological basis, Jean Piaget is a cognitive psychology figure who had a great influence on the development of thinking of other cognitive experts. According to Piaget, cognitive development is a genetic process, which is a process based on the biological mechanism of the development of the nervous system. The philosophical foundation uses the philosophy of constructivism, the theoretical basis uses the theory of teacher values ??with character. This study used a qualitative approach and data collection techniques were carried out through triangulation of observations, interviews and documentation studies, while the source of data was through triangulation of principals, teachers and students. Key words: Development, Through, Character